IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN PADA PESERTA DIDIK DI SD NEGERI 187/1 TERATAI - Chan, Faizal; Kurniawan, Agung Rimba; Melinda, Lia Gusti; Priantini, Rattu; Zubaedah, Zubaiedah; Suharti, Siti Reni; Khodijah, Siti (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This study aims to determine and describe the implementation of discipline character education for students in elementary schools. Discipline character is one of the character values that are in the core competencies of social attitudes that must be developed in both students. This study uses a qualitative research approach. This type of research is descriptive research. This research was carried out in Teratai Muara Bulian Elementary School 187/1. This research was conducted in a period of two months (August - September). Data and data sources used are primary data and secondary data. Data sources taken in this study are 1) observation data, 2) school principal data, 3) teacher data, 4) student data. The technique of sample collection in this study was purposive sampling. Data collection techniques, namely 1) observation, observation used is non-participant observation. 2) interview, the interview used is a structured interview. Interviews were conducted with the school principal and class teacher. Data analysis using military and Huberman analysis techniques. Activities in data analysis, namely data reduction, data display (data presentation), and data conslusion (drawing conclusions). This research instrument is based on two sources, according to the Ministry of National Education (2010: 26) indicators of the value of discipline are: "1) getting used to being present on time; 2) getting used to obey the rules; and 3) using clothes in accordance with the provisions "and according to Syafrudin (Muhammad Khafid and Suroso, 2007: 91) are:" 1) observance of study time; 2) observance of lesson assignments; 3) obedience using the time of coming and going home ". The results showed that the implementation of discipline character education in SD N 187/1 Lotus lotus estuary was carried out adequately. The results obtained are related to the discipline value indicator.